Development of Electrical Machine Training Kits to Increase Competency in Practical Learning and Work Readiness in The Industry - Budiastuti, Pramudita; Damarwan, Eko Swi; Triatmaja, Adhy Kurnia; Setyanto, Barry Nur (Elinvo (Electronics, Informatics, and Vocational Education), 2023)
This study aims to develop Electrical Machine Training Kit for electrical machine practice media in vocational education. This type of research with Analyze, Design, Development, Implementation, and Evaluation (ADDIE) model. The background of this research is that the need for electrical machine competency, which students should have mastered, is still insufficient due to inadequate tools. Many graduates still have difficulty getting a job in the industry because competence has not been fulfilled during college. Electronic engineering vocational education is a study program that has the goal of producing superior graduates in achieve electrical machine competence and being ready to work in the industry. Electronic engineering vocational education is a new study program that is still in the development stage to achieve this goal. The media aspect obtains a minimum value of 87.5% and a maximum value of 90%. Material aspects get a value of 88.40% for suitability material and 90.2% for the quality of learning. The user feasibility test obtained a value of 89.80% in review from motivation, 88.0% in terms of convenience, and 90.3% in terms of material. It is concluded that the Electrical Machine Training Kit is included in the "very feasible" category.